Bacterial toxins in musculoskeletal infections. Issue 2 (14th April 2020) - Saeed, Kordo; Sendi, Parham; Arnold, William V.; Bauer, Thomas W.; Coraça‐Huber, Débora C.; Chen, Antonia F.; Choe, Hyonmin; Daiss, John L.; Ghert, Michelle; Hickok, Noreen J.; Nishitani, Kohei; Springer, Bryan D.; et al.
Abstract: Musculoskeletal infections (MSKIs) remain a major health burden in orthopaedics. Bacterial toxins are foundational to pathogenesis in MSKI, but poorly understood by the community of providers that care for patients with MSKI, inducing an international group of microbiologists, infectious diseases specialists, orthopaedic surgeons and biofilm scientists to review the literature in this field to identify key topics and compile the current knowledge on the role of toxins in MSKI, with the goal of illuminating potential impact on biofilm formation and dispersal as well as therapeutic strategies. The group concluded that further research is needed to maximize our understanding of the effect of toxins on MSKIs, including: (i) further research to identify the roles of bacterial toxins in MSKIs, (ii) establish the understanding of the importance of environmental and host factors and in vivo expression of toxins throughout the course of an infection, (iii) establish the principles of drug‐ability of antitoxins as antimicrobial agents in MSKIs, (iv) have well‐defined metrics of success for antitoxins as antiinfective drugs, (v) design a cocktail of antitoxins against specific pathogens to (a) inhibit biofilm formation and (b) inhibit toxin release. The applicability of antitoxins as potential antimicrobials in the era of rising antibiotic resistance could meet the needs of day‐to‐day clinicians.